ANTICANCER ACTIVITY OF ETHANOLIC EXTRACT OF Selaginella plana HIERON. ON T47D CELL LINE IN VITRO - Chandra Risdian; Sri Handayani; Zalinar Udin; Rina Andriyani; Marissa Angelina (Jurnal Kimia Terapan Indonesia, 2011)
Selaginella sp belongs to the Selaginellaceae family. It has been used in China and Indonesia as a traditional medicine. It hasseveral medicinal properties including antibacterial, anticardiovascular, and anticancer agent. The aim of the present study was to access the anticancer property of the ethanolic  extracts of Selaginella plana Hieron. on T47D breast cancer cell line. The proliferation of T47D cell line was detected by SRB (Sulforhodamine B) assay which was measured at a wavelength of 515 nM. The result showed that the IC50 of the ethanolic extract was determined at 7.03 pg/mL. This significant activity was assumed due to its high total flavonoid content. The totalflavonoid content of the ethanolic extract was 23.04%. Flow cytometry analysis indicated that the extract may undergo the cell death via apoptosis pathway. In conclusion, the ethanolic extract of Selaginella plana Hieron: has considerable activity in inhibiting T47D cell line proliferation.Key words: Selaginella plana Hieron., SulforhodamineB, T47Dcells, anticancer flow cytometry